2017
DOI: 10.2174/1574886311666160719154420
|View full text |Cite
|
Sign up to set email alerts
|

Safety Considerations in the Use of Ketorolac for Postoperative Pain

Abstract: Perioperative administration of ketorolac has been demonstrated to be safe and effective in healthy patients and is particularly beneficial as an opioid-sparing agent in vulnerable patient groups. However, in certain surgical and medical contexts, proper patient selection based on the multidisciplinary collaboration between perioperative clinician specialists will optimize patient safety and pain management outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Bleeding risk has been of primary concern with perioperative NSAID exposure given the anti-platelet effects of cyclooxygenase-1 (COX-1) inhibition. Bleeding times and postoperative bleeding events do not appear significantly affected by NSAIDs at usual doses, and this risk may be further mitigated by using COX-2 selective agents [211][212][213][214][215][216]. Traditional dogma has suggested avoiding NSAIDs in spinal/orthopedic fusion surgeries because of the risk of nonunion.…”
Section: Preoperative Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding risk has been of primary concern with perioperative NSAID exposure given the anti-platelet effects of cyclooxygenase-1 (COX-1) inhibition. Bleeding times and postoperative bleeding events do not appear significantly affected by NSAIDs at usual doses, and this risk may be further mitigated by using COX-2 selective agents [211][212][213][214][215][216]. Traditional dogma has suggested avoiding NSAIDs in spinal/orthopedic fusion surgeries because of the risk of nonunion.…”
Section: Preoperative Phasementioning
confidence: 99%
“…Since inflammation is a key driver of pain after surgery, early anti-inflammatories may be the most effective postoperative analgesic strategies, as evidenced by their superior performance over opioids in analyses of randomized controlled studies [164,[393][394][395][396]. Novel intravenous formulations of ibuprofen and diclofenac currently have limited roles in therapy due to a lack of demonstrated superiority to ketorolac and significantly higher cost [214,215]. Escalating doses of ketorolac greater than 10-15 mg per dose and ibuprofen greater than 400 mg per dose may offer additional analgesic benefit, and the duration of ketorolac therapy should generally be limited to no more than 5 days [212,[397][398][399][400].…”
Section: Postoperative Nonopioid Considerationsmentioning
confidence: 99%
“…34-35 There is ongoing concern regarding increased postoperative hemorrhage when ketorolac is used for analgesia, but there is conflicting evidence regarding the safety of ketorolac in pediatric tonsillectomy. 36-37…”
Section: Discussionmentioning
confidence: 99%
“…[34][35] There is ongoing concern regarding increased postoperative hemorrhage when ketorolac is used for analgesia, but there is conflicting evidence regarding the safety of ketorolac in pediatric tonsillectomy. [36][37] The anesthesiologists who do use opioids in the PACU for a normal-weight child with severe OSA are most likely to use fentanyl (51.8%) which has a rapid onset and short duration of action. 33 There is an increase in analgesic and respiratory sensitivity to opioids in children with severe OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Ketorolac is preferred to morphine in managing acute pain because, contrary to morphine, it does not have adverse effects on the central nervous system and does not cause respiratory depression and hypotension. Moreover, morphine reduces the movement of the digestive tract and may cause itching or allergic reactions; furthermore, the chronic use of morphine can lead to drug dependence (25). In addition, research has shown that ketorolac has proper efficacy in 25 to 50% of cases when compared to opiate drugs.…”
Section: Discussionmentioning
confidence: 99%